The Influence of Live Streaming, Customer Trust and Pro-Domestic Ethnocentrism on Purchase Intention with Customer Attitude as a Mediation Variable on Local Fashion Brand Products Through Tiktok - Sari, Rahmi Putri; Syafrizal; Lenggogeni, Sari (SAFE-Network, 2023)
The presence of e-commerce and online trading platforms has enabled and directed people to buy goods online anywhere and anytime. Sellers can choose various online trading methods that best suit the business model, one of which is live streaming through the Tiktok social media platform. This study aims to investigate the effect of Prodomestic Etnocentrism, Customer Trust and Live Streaming on Purchase Intention wich are mediated by customer trust. Online survey was applied to 160 respondents. Research instruments were adapted from previous studies. Structural equation modelling was applied to analyzed the data of this research by using Smart PLS 4.0 software. The results showed that live streaming and customer trust have an important and meaningful impact on customer attitudes. The impact of live streaming, customer trust, and customer attitude on purchase intention is significant. This study also found the significant role of attitude in mediating relationship between live streaming and customer trust towards purchase intention. But, pro-domestic ethnocentrism didn’t have significant effect to both of customer attitude and purchase intention in Tiktok.